A spatial micro-econometric approach to estimating climate change impacts on wine firm performance: A case study from Moldavia region, Romania. (December 2015) - De Salvo, Maria; Begalli, Diego; Capitello, Roberta; Signorello, Giovanni
Abstract: This article proposes a micro-econometric approach to assess climate change impacts on wine industry performance in the Moldavia region of Romania. In the assessment we consider the spatial variability of wine-growing micro-areas and employ a small scale for the analysis. Results show that vineyard revenue is influenced by a local effect. Spatial differences among municipalities are highlighted and are driven by vineyard locations and distance from urban areas. Differences at the local scale reflect the presence of structural and environmental constraints. Findings demonstrate that climate change impacts vary significantly among simulated scenarios. The simulated increase in temperature should compensate for the negative effect caused by rainfall changes. Results also suggest that winegrowers should benefit from climate change, although this will depend on the vineyard's location. Potential policy measures designed to remove local constraints and to capitalise on the positive effects of climate change are discussed. Highlights: The study focuses on the importance of local and spatial effects. The Moldavian wine region (Romania) is considered as a case study. Farms and environmental constraints limit profitability in the south Moldavia. Vineyards close to urban centres experience higher profitability. Results show that the Moldavian wine industry will benefit from climate change.